Single cell electron collectors for highly efficient wiring-up electronic abiotic/biotic interfaces - Yu, Yang-Yang; Wang, Yan-Zhai; Fang, Zhen; Shi, Yu-Tong; Cheng, Qian-Wen; Chen, Yu-Xuan; Shi, Weidong; Yong, Yang-Chun (Nature communications, 2020)
By electronically wiring-up living cells with abiotic conductive surfaces, bioelectrochemical systems (BES) harvest energy and synthesize electric-/solar-chemicals with unmatched thermodynamic efficiency. However, the establishment of an efficient electronic interface between living cells and abiotic surfaces is hindered due to the requirement of extremely close contact and high interfacial area, which is quite challenging for cell and material engineering. Herein, we propose a new concept of a single cell electron collector, which is in-situ built with an interconnected intact conductive layer on and cross the individual cell membrane. The single cell electron collector forms intimate contact with the cellular electron transfer machinery and maximizes the interfacial area, achieving record-high interfacial electron transfer efficiency and BES performance. Thus, this single cell electron collector provides a superior tool to wire living cells with abiotic surfaces at the single-cell level and adds new dimensions for abiotic/biotic interface engineering. Efficient management of electron transfer between living cells and solid abiotic surfaces is quite challenging. Here, the authors report the assembling of single cell electron collector for individual cell to promote the biotic/abiotic interfacial electron transfer at the single-cell level.